2012
DOI: 10.1186/1471-2407-12-520
|View full text |Cite
|
Sign up to set email alerts
|

Serological identification of Tektin5 as a cancer/testis antigen and its immunogenicity

Abstract: BackgroundIdentification of new cancer antigens is necessary for the efficient diagnosis and immunotherapy. A variety of tumor antigens have been identified by several methodologies. Among those antigens, cancer/testis (CT) antigens have became promising targets.MethodsThe serological identification of antigens by the recombinant expression cloning (SEREX) methodology has been successfully used for the identification of cancer/testis (CT) antigens. We performed the SEREX analysis of colon cancer.ResultsWe isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…None of the healthy donor serum was reactive. Three serum samples from the same panel of sera were also reactive against TEKT5 [32]. Taken together, these findings suggest that the serologically-defined CT antigens, CCDC62-2, GKAP1, and TEKT5, may provide a molecular basis for diagnostic and immunotherapeutic targets in HNSCC patients.…”
Section: Expression and Humoral Response Of Ct Antigens To Hnsccmentioning
confidence: 76%
See 3 more Smart Citations
“…None of the healthy donor serum was reactive. Three serum samples from the same panel of sera were also reactive against TEKT5 [32]. Taken together, these findings suggest that the serologically-defined CT antigens, CCDC62-2, GKAP1, and TEKT5, may provide a molecular basis for diagnostic and immunotherapeutic targets in HNSCC patients.…”
Section: Expression and Humoral Response Of Ct Antigens To Hnsccmentioning
confidence: 76%
“…Hanafusa et al performed SEREX analysis on colon cancer, and identified the novel CT antigen, Tektin 5 (TEKT5) [32]. TETKs are composed of a family of filament-forming proteins in the male germ cell-lineage in centrioles and basal bodies and within ciliary and flagellar doublet microtubules [64].…”
Section: Tekt5mentioning
confidence: 99%
See 2 more Smart Citations
“…To date, more than 600 tumor-associated antigens have been identified using by SE-REX [9,10]. Most of the SEREX-based studies aimed at the identification of novel tumor antigens that elicit an antibody response in tumor tissue or cell lines [11][12][13][14][15][16]. Until now, there was no antigen identified by SEREX based on tumor stem cell, which is notorious for GBM recurrence and malignance [5,17,18].…”
Section: Introductionmentioning
confidence: 99%